1997
DOI: 10.1002/eji.1830270136
|View full text |Cite
|
Sign up to set email alerts
|

CD28‐mediated induction of proliferation in resting T cells in vitro and in vivo without engagement of the T cell receptor: Evidence for functionally distinct forms of CD28

Abstract: JJ316 and JJ319 are rat CD28-specific monoclonal antibodies (mAb) of the gamma1 kappa isotype with identical co-stimulatory potency. At a concentration 100-1000-fold higher than that required for co-stimulation, JJ316, but not JJ319 induces massive proliferation of all T cell subsets in vitro without T cell receptor (TCR) triggering. "Direct" stimulation by JJ316 is fully blocked by JJ319, indicating that it is not due to cross-reactivity of JJ316 with the TCR complex or other activating receptors. JJ316 binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
134
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 153 publications
(145 citation statements)
references
References 39 publications
10
134
0
1
Order By: Relevance
“…5-7). In agreement with our earlier findings that all CD4 T cells undergo DNA synthesis in response to CD28 stimulation [32], we observed that also in the CD25 -subset, a high degree of cycling is observed on day 1 after stimulation ( Fig. 5).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…5-7). In agreement with our earlier findings that all CD4 T cells undergo DNA synthesis in response to CD28 stimulation [32], we observed that also in the CD25 -subset, a high degree of cycling is observed on day 1 after stimulation ( Fig. 5).…”
Section: Discussionsupporting
confidence: 93%
“…This also holds true for the rat [31], where in addition, we have previously described a class of "superagonistic" CD28-specific mAb which are able to induce proliferation of all T cell subsets without the need for TCR engagement [32]. Importantly, CD28 superagonists are also active in vivo, where in response to a single mAb injection, CD4 T cell numbers in peripheral lymphoid organs rise fivefold within 3 days before returning to base line levels [32].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Une forme soluble de CTLA-4 (sCTLA-4) a été décrite, dont l'expression est augmentée dans les celle d'interleukine (IL)-2, l'expression du récepteur de l'IL-2 [3][4][5], la survie cellulaire via l'expression accrue des molécules anti-apoptotiques dont Bcl-X L [6]. Il existe des signaux activés par CD28 indé-pendamment de l'activation antigénique comme cela a été démontré par l'utilisation d'anticorps monoclonaux (Acm) anti-CD28 nommés superagonistes [7]. L'analyse des mécanismes transcriptionnels et post-transcriptionnels régulés par CD28 a permis de démontrer que cette molécule contrôle l'expression et l'activité des facteurs de transcription NFAT (nuclear factor of activated T-cells), NF-kB et AP-1 sur le promoteur du gène de l'IL-2 [8,9].…”
Section: Ctla-4 : Structure Distributions Cellulaire Et Tissulaireunclassified